PENGUASAAN HAK ASUH ANAK AKIBAT PERCERAIAN PERSPEKTIF HUKUM ISLAM DAN UNDANG UNDANG DASAR - Muhammad Muhammad; Ahmad Mustafid Alfiyan (JOURNAL SAINS STUDENT RESEARCH, 2026)
One of the biggestkimpacts ofkdivorce is on the child kof both partners. After divorcekoccurs, it will affect the lchild's life, especially in kthe lfamily, community, kschool, play and getkalong. Therefore, the resolution kof the case of kmastery ofk childcare (hadhanah) mustl pay attention tok the kindness kof ( be advised ) lchildren. Of; course, in the Islamick law ythe determinationk of child custody has been regulated, the legal istinbath by the cleric becomes onem of the references tov the determination of the law in thisk case namely childx custody.The type lof researchl used xis the literaturex study (libraryb research ). Dataz sources are primaryt data sources and secondaryn data sourcesx. Datak collection techniquezs useyx in researchl areb libraxry. The datan analysis techniquze usedd is qualitative analysis, thatl is, aftern the data is collected then analyzes using content analysis and discourse analysis methods.Theo results of thivs study includez: that in thiys caseb Islamicm law provides some views on the establishment of Islamic law ( Imam Malik, Imam Shafi’i, and Imam Hanafi) arguez that the masteryu of childcarex (hadhanah) dueb tto divorce is carried out by kMother, Imam Malik, Imam Shafi'i, and Imam Hanafi kagreed lthat it kwas Mother lwho waly mostb entitled qol carez for children, if divorceol loccurs. Thelbasis of thekconsideration of lImam Malik, Imam Shafi'i, and yImam Hanafi lpicking up childcare due to divorce ie mothers have more affection compared to fathers